Production of biodegradable polymer via graft copolymerization of gum Arabic and polyethylene glycol - Rifkatu Kambel, Dogara; Jibrin Muhammad, Yelwa; Zaccheus, Shehu; Fatima, Soye (Journal of Polymer Science Research, 2023)
The increasing demand for environmentally-friendly materials has led to a surge in research on the production of biodegradable polymers. In this study, we investigate the synthesis of a biodegradable polymer by graft copolymerization of gum Arabic (GA) and polyethylene glycol (PEG). GA, a natural polysaccharide and PEG, a synthetic water-soluble polymer, were used as the backbone and graft monomer, respectively. The graft copolymerization was carried out using benzoyl peroxide as an initiator and performed under nitrogen atmosphere. The resulting polymer was characterized by Fourier transform infrared (FTIR) spectroscopy, Xray diffraction (XRD), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). The FTIR spectra confirmed the formation of the graft copolymer, and TGA analysis showed that the copolymer had higher thermal stability than GA. The DTA thermograms indicated two thermal events. The evaporation of water and organic polyethylene glycol components was measured, and the first mass loss was due to the loss of adsorbed and structural water in the gum Arabic, which occurred between 31.87 and 180°C, while the second, corresponding to the pyrolysis of polyethylene glycol functional groups and polysaccharide decomposition, resulted in a 70% mass loss. SEM morphological analysis of gum Arabic showed aggregates of high irregularity in particle shape. The cracks and holes obtained in the Gum Arabic micrograph disappeared from the new gum Arabic-graft-polyethylene glycol, leaving a smooth surface with scattered particles in the image, which was due to the grafting copolymer. From the XRD patterns, the percentages of the amorphous and crystalline phases were determined. The results show that gum Arabic has a 78% degree of crystallinity, whereas gum Arabic-graft-polyethylene glycol has the lowest value of 51%. Biodegradation activity was observed using the fungus Aspergillus flavus on different days on gum Arabic-g-polyethylene glycol. The results clearly showed inhibition zones with a change in the state of the copolymer from solid to liquid from days 8 to 14. These results indicate that the GA-PEG copolymer has potential as a biodegradable material for use in various applications, such as packaging, agriculture, and medical industries.
Keywords: Graft copolymerization; Gum Arabic; polyethylene; biodegradable polymer